The Rise of the Khalwatiyah Sammān Sufi Order in South Sulawesi: Encountering the Local, Escaping the Global - Ubaedillah, Achmad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
The rise of the Khalwatīyah Sammān Sufi Order (tarekat) in South Sulawesi in the second half of the nineteen century should not be seen as just another local religious phenomenon. The rapid growth of its reputation among commoners occurred in conjunction with the influence of global Islam brought to the area in the form of Wahabism from the Haramayn (Mecca and Medina), the center of Islam, and the local political consequences of the Bongaya Treaty between the ruler of Gowa and the Dutch in 1667. The political and social grievances the Treaty caused on the one hand and the religious elitism of formal religious leaders (parewa sarak) on the other also contributed to the impact the order was to have. The commoners widely accepted the order because of its uncomplicated way of the performance of its ritual (dhikr), while the patronage of its leaders with the royal members offered local power holders added to the order’s popularity among the elites.DOI: 10.15408/sdi.v24i2.4186